The Discourse of the ʿUlamā’ on the Boko Haram Phenomenon in Northern Nigeria: An Appraisal of the Debate between ʿIsa ʿAli Pantami and Muhammad Yusuf, the leader of Boko Haram (American Journal of Islam and Society, 2025)
Prior to the nominal suppression of the Boko Haram group and the subsequent killing of its founder, Muhammad Yusuf, in 2009, many Nigerians (including the majority of Muslims) knew very little about the extremist organization. Likewise, it was not widely known that some Muslim scholars, especially mainstream Sunnis, had engaged the spiritual leaders of the group in an ideological dialogue a few years after its emergence. Yet, interested parties had sought to link Boko Haram’s militancy to the increasingly prominent, Salafi style of religious propagation. Fortunately, those attempts were nullified by the emergence of well-documented debates and dialogues advanced by Sunni scholars. This article presents the discourse of Nigerian scholars about Boko Haram’s ideology. In particular, it analyses a debate that took place between ‘Isa ‘Ali Pantami and Muhammad Yusuf. Using a video recording of the debate and key academic literature, this essay finds that a weak and misguided perception of the objectives of the Islamic Sharī’ah and the desire of undue fame, among other factors, are the main issues that led to the emergence, growth and militancy of the organization.